Comparative analysis of clinical and electroneuromyographic indicators in patients with secondary polyneuropathy - Ye. S. Korolyova; R. B. Tsyrenzhapova; V. M. Alifirova; N. S. Novikova (Бюллетень сибирской медицины, 2012)
Analysis of clinical and electroneuromyographic performance of two groups of patients with secondary polyneuropathy showed that diabetic neuropathy affects the peripheral nerves of the lower extremities, whereas in polyneuropathy of mixed etiology (paraneoplastic and toxic) in the pathological process involved both nerve fibers, the low and upper extremities.